Mobile wave crawler for energy generation: Preliminary feasibility and opportunities for Bangladesh (Journal of Bangladesh Academy of Sciences, 2025)
One of the major challenges for a densely populated country like Bangladesh is energy shortage. For electricity generation, the country mostly relies on fossil fuels such as furnace oil, natural gas, and coal. With the environmental problems associated with fossil fuels, the global transition to renewable energy sources is inevitable. Ocean waves represent a promising renewable energy source in this regard. A large area of Bangladesh is covered by the sea, which offer significant potential for wave energy. Wave energy can be converted into electricity using a range of devices, including point absorbers, attenuators, wave surge devices, and oscillating water columns. However, these devices are fixed at specific locations, depend on particular wave profiles, and require expensive underwater cables. Against this background, the Mobile Wave Crawler (MWC), an autonomous wave energy converter, appears to be a promising solution. This work assesses the feasibility of the device, and evaluates its potential energy output. It also demonstrated a levelized cost of energy (LCOE) of USD 0.12 kWh for an energy-producing machine with an hourly rated capacity of 1 MW. Although this cost is higher than of traditional fossil-fuel-based power plants, the technology can be promoted as sustainable and environmentally friendly. This research illustrates that the proposed solution is a feasible source of green energy for the offshore islands of Bangladesh, identifies the major challenges, and suggests possible solutions. In addition, the study estimates the required number of Mobile Wave Crawlers for several example islands. For instance, four MWC units are required for each of Bhashan Char and Shah Porir Dwip, while only one unit is required for each St. Martin's Island and Dublar Char to meet their respective energy demands.J. Bangladesh Acad. Sci. 49(2); 215-225: December 2025